STEM Learning in Early Childhood Education: Preparing a Smart Generation from an Early Age - Taufikin Taufikin (Pt. Anagata Sembagi Education, 2025)
STEM learning has become an essential foundation in early childhood education due to its capacity to strengthen scientific reasoning, computational thinking, collaboration, communication, and creativity from the earliest years of development. This study employs a systematic literature review of 38 empirical and conceptual publications within the last decade to examine how STEM learning prepares a smart generation from an early age. The results reveal that hands-on scientific inquiry, digital and robotics-enhanced learning, STEAM creativity integration, and culturally contextual STEM programs consistently promote analytical reasoning, motivation, resilience, and innovative thinking. Sustainability, however, requires teacher readiness, strong school leadership, active parental involvement, resource continuity, and time allocation that protects inquiry-based play. This study contributes by synthesizing a conceptual map of the pedagogical and institutional components necessary for STEM to successfully support future-ready development in early childhood